Analisis Pengaruh Current Ratio dan Debt to Equity Ratio terhadap Return on Assets pada Perusahaan Transportasi dan Logistik yang Terdaftar di BEI Periode 2020-2024 - Zildanis, Zahra; Nurhadi; Hadi, Seno Sudarmono (CV Warnak Johanna Nusantara, 2026)
Abstracts - This study aims to analyze the influence of the current ratio and debt to equity ratio on return on assets in transportation and logistics companies listed on the Indonesia Stock Exchange (IDX) for the period 2020–2024. The population in this research consists of 37 transportation and logistics companies. The data used is secondary data obtained from the companies' financial statements for the 2020–2024 period. The sampling technique used is purposive sampling, where samples are selected based on specific criteria determined by the researcher, resulting in 10 companies being chosen as research samples. The results of the study show that: (1) the current ratio has a partially significant effect on return on assets, indicated by a t-value of (3.594 > 2.010); (2) the debt to equity ratio has no significant partial effect on return on assets, with a t-value of (0.067 < 2.010); and (3) the current ratio and debt to equity ratio simultaneously have a significant effect on return on assets, as shown by an F-value of (6.753 > 3.195) in transportation and logistics companies listed on the IDX during the 2020–2024 period.